Human exceptionalism, our ordinary cortex and our research futures. Issue 3 (27th February 2019) - Finlay, Barbara L.
Abstract: The widely held belief that the human cortex is exceptionally large for our brain size is wrong, resulting from basic errors in how best to compare evolving brains. This misapprehension arises from the comparison of only a few laboratory species, failure to appreciate differences in brain scaling in rodents versus primates, but most important, the false assumption that linear extrapolation can be used to predict changes from small to large brains. Belief in the exceptionalism of human cortex has propagated itself into genomic analysis of the cortex, where cortex has been studied as if it were an example of innovation rather than predictable scaling. Further, this belief has caused both neuroscientists and psychologists to prematurely assign functions distributed widely in the brain to the cortex, to fail to explore subcortical sources of brain evolution, and to neglect genuinely novel features of human infancy and childhood.